Assessing hydrological processes controlling the water balance of lakes in the Peace-Athabasca Delta, Alberta, Canada using water isotope tracers - Falcone, Matthew (University of Waterloo, 2007)
One of the world’s largest freshwater deltas (~4000 km2), the Peace-Athabasca Delta (PAD), is located at the convergence of the Peace and Athabasca rivers and Lake Athabasca in northern Alberta, Canada. Since the early 1970s, there has been increasing concern regarding the ecological impacts on the PAD after flow regulation of the Peace River began in 1968, decreased discharge in the Peace and Athabasca rivers as a result of hydroclimatic changes in Western Canada, and increased Athabasca River water usage by oil sands development to the south. This thesis is part of an ongoing, multi-disciplinary project assessing current and past hydrological and ecological conditions in the PAD. Research conducted in this thesis aims to better understand the processes controlling water balance of lakes in the PAD using mainly stable water isotope data collected from lakes and their input sources. Isotope data are used to describe and quantify hydrological processes for individual lakes (seasonal and annual) and across the delta and are supported by other chemical and hydrometric data. An isotopic framework in d18O-d2H-space is developed for the PAD using evaporation-flux-weighted local climate data, and isotopic data collected from a reference basin, lakes throughout the PAD, and lake input sources (i.e., snowmelt, rainfall, and river water). The framework is comprised of two reference lines, the Local Meteoric Water Line, which is based on measured isotopic composition of precipitation, and the Local Evaporation Line, which is based on modelled isotopic composition of reference points. Evaporation pan data is used to assess short-term variations in key isotopic reference values, which are important for addressing short-term changes in the isotopic signature of shallow basins. This framework is used in subsequent chapters including assessment of seasonal and annual water balance of two hydrologically-contrasting shallow lakes, and to quantify the impacts of flood water and snowmelt on a set of 45 lakes in spring 2003. Five ...